A survey on Number plate recognition systems (International Journal of Engineering and Computer Science, 2017)
Now in these days the traffic on road is increases much frequently. In addition of that to manage the road traffic various efforts are also prepared. In this context the vehicle number plate recognition is a valuable step to identify the vehicle and their identity. In this paper the review of such kind of vehicle recognition system is prepared. In addition of that for improving the accuracy of number plate recognition a new model based on existing technique is prepared. That model claims to provide the efficient and accurate recognition. In addition of that the future extension of the proposed work is also included.